DOES BRAND ATTITUDE AFFECT THE FINANCIAL DECISION-MAKING BEHAVIOUR OF MALAYSIAN MILLENNIALS IN PURCHASING SHARIAH-COMPLIANT STOCKS? - Mohd Feroz Shah De Costa; Norzalita Abd Aziz (International Journal of Accounting, Finance and Business, 2019)
This study pursues to ascertain whether having a favourable brand attitude towards a company will be a determinant factor for millennials in deciding to purchase Shariah- compliant online shares. This study also examined the influence of online financial communication on millennials’ brand attitude via firm generated content and user generated content. This study collected data from 308 potential millennial retail investors in Malaysia using the convenience sampling procedure. The partial least squares structural equation modelling (PLS-SEM) technique and the SmartPLS 3 tool was used to examine the data. This study contributes to the research areas of financial communication and Islamic financial services marketing in relevance to Shariah-compliant online shares, signalling theory and provides significant managerial implications for investor relations managers.